A new approach for probing matter in periodic nanoconfinements using neutron scattering. (1st August 2014) - Ashkar, Rana; Pynn, Roger; Dalgliesh, Robert; Lavrik, Nickolay V.; Kravchenko, Ivan I.
Abstract : The efficacy of spin‐echo small‐angle neutron scattering (SESANS) combined with an exact dynamical theory (DT) model in resolving the arrangement of spherical colloidal particles in planar confinements, such as the channels of a rectangular diffraction grating, is reported. SESANS data obtained with a suspension of charge‐stabilized 180 nm silica particles in contact with a silicon diffraction grating, with ∼650 nm‐wide channels, show clear deviations from the signal expected from a homogenous distribution of the suspension. DT fits to the data indicate that the colloidal particles are almost twice as concentrated in the channels as they are in the neighboring bulk suspension, consistent with a structure in which the particles are arranged in close‐packed sheets parallel to the walls of the confining channels.